Impact of Anti-Inflammatory Drugs on Pyogenic Vertebral Osteomyelitis: A Prospective Cohort Study. (19th October 2016) - Dinh, Aurélien; Jean, Maxime; Bouchand, Frédérique; Davido, Benjamin; Descatha, Alexis; Duran, Clara; Gras, Guillaume; Perronne, Christian; Mulleman, Denis; Salomon, Jérôme; Bernard, Louis
Abstract : Objective . Pyogenic vertebral osteomyelitis (PVO) are frequently misdiagnosed and patients often receive anti-inflammatory drugs for their back pain. We studied the impact of these medications. Methods . We performed a prospective study enrolling patients with PVO and categorized them depending on their drugs intake. Then, we compared diagnosis delay, clinical presentation at hospitalization, incidence of complications, and cure rate. Results . In total, 79 patients were included. Multivariate analysis found no correlation between anti-inflammatory drug intake and diagnosis delay, clinical presentation, complications, or outcome. Conclusion . Anti-inflammatory drugs intake does not affect diagnostic delay, severity at diagnosis, or complications of PVO.